URBANISASI DAN DAYA DUKUNG LINGKUNGAN DI KOTA TANGERANG - Gusti Ayu Ketut Surtiari (Pusbindiklat - LIPI, 2009)
The purpose of this article is to know the condition of the carrying capacity of Tangerang City. The background is that Tangerang City has rapidly increased in development and population growth according to its location as a Buffer zone ofD KI Jakarta and a central of industry. A Buffer zone is hoped to be able to counter the high population growth in Jakarta by creating a harmonious development between Jakarta and its surroundings. Tangerang City acts as housing for commuters to Jakarta and have to accommodate migrants who want to work in Tangerang City. The development of housing and its facilities increase the utilization of natural resources such as land and water. Otherwise, the natural resources have limitation of capacity. The over utilization will encourage the risk of land degradation that can threaten a sustainable urban development. For its purpose, this article used data from BPS publication and other related sources, and it was analyzed descriptively.